2016
DOI: 10.2147/ijwh.s122781
|View full text |Cite
|
Sign up to set email alerts
|

Success rate in preterm uterine contraction inhibition with tocolytic agents in a tertiary care center

Abstract: ObjectiveThis study aims to assess the success rate of inhibiting preterm uterine contraction with tocolytic agents to delay delivery for at least 48 hours and risk factors of failure inhibition.Materials and methodsBetween January 2013 and July 2014, medical records of all singleton pregnant women between 24 0/7 and 33 6/7 weeks of gestation with the diagnosis of preterm labor (with cervical dilatation) or threatened preterm labor (without cervical dilatation) who received tocolytic agents were reviewed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…This study found the rate for successful preterm labor pain for at least 48 hours for 54.29% whereas the previous studies Theplib A. and Phupong V. found the rate for successful preterm labor pain at 83.4% [4] and the study of Kiasuda D. and colleague found the rate for successful preterm labor pain at 86.4% [5]. Maharat Nakhon Ratchasima Hospital is a tertiary referral hospital which accepts referrals from Secondary care center.…”
Section: Table 1 Baseline Maternal Characteristics Of Pregnant Women mentioning
confidence: 59%
“…This study found the rate for successful preterm labor pain for at least 48 hours for 54.29% whereas the previous studies Theplib A. and Phupong V. found the rate for successful preterm labor pain at 83.4% [4] and the study of Kiasuda D. and colleague found the rate for successful preterm labor pain at 86.4% [5]. Maharat Nakhon Ratchasima Hospital is a tertiary referral hospital which accepts referrals from Secondary care center.…”
Section: Table 1 Baseline Maternal Characteristics Of Pregnant Women mentioning
confidence: 59%
“…Sample size was calculated based on the findings of Kiatsuda et al 19 that UTI or ASB were presented in 15.5% of women admitted with preterm labor or threatened preterm labor. With alpha of 0.05 and d= 0.015, the sample size needed was 2,237 women.…”
Section: Methodsmentioning
confidence: 99%